1996
DOI: 10.1289/ehp.96104s1123
|View full text |Cite
|
Sign up to set email alerts
|

Implications for risk assessment of suggested nongenotoxic mechanisms of chemical carcinogenesis.

Abstract: 123-134 (1996)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 98 publications
1
53
1
1
Order By: Relevance
“…DCB is a nongenotoxic agent (Loeser and Litchfield, 1983;NTP, 1987;Steinmetz et al, 1988), which appears to produce an additive hyperplasia in rodent liver and a regenerative hyperplasia in male rat kidney. While increased cell proliferation has been implicated in the formation of tumors in rodents by various classes of nongenotoxic carcinogens (Loury et al, 1987;Butterworth, 1991;Cohen and Ellwein, 1991;Grasso and Hinton, 1991;Ames et al, 1993;Lake, 1995;Cunningham, 1996;Lake and Grasso, 1996), a correlation between increased cell replication and carcinogenesis is not always observed (Melnick and Huff, 1993;Melnick et al, 1996). In the present study replicative DNA synthesis was increased in both species after acute DCB treatment, whereas in the NTP bioassay DCB produced liver tumors only in the mouse.…”
Section: Discussioncontrasting
confidence: 48%
“…DCB is a nongenotoxic agent (Loeser and Litchfield, 1983;NTP, 1987;Steinmetz et al, 1988), which appears to produce an additive hyperplasia in rodent liver and a regenerative hyperplasia in male rat kidney. While increased cell proliferation has been implicated in the formation of tumors in rodents by various classes of nongenotoxic carcinogens (Loury et al, 1987;Butterworth, 1991;Cohen and Ellwein, 1991;Grasso and Hinton, 1991;Ames et al, 1993;Lake, 1995;Cunningham, 1996;Lake and Grasso, 1996), a correlation between increased cell replication and carcinogenesis is not always observed (Melnick and Huff, 1993;Melnick et al, 1996). In the present study replicative DNA synthesis was increased in both species after acute DCB treatment, whereas in the NTP bioassay DCB produced liver tumors only in the mouse.…”
Section: Discussioncontrasting
confidence: 48%
“…Exposure to phenobarbital, benzene, asbestos, and arsenic even without the previous application of initiator agents leads to neoplasic development (Melnick et al 1996, Trosko 2001). This contradiction has two possible explanations: either the genotoxic effect was not identified by mutagenicity and genotoxicity assays, or the initiated cells emerged spontaneously.…”
Section: Promotionmentioning
confidence: 99%
“…Increased cell proliferation, as indicated by proliferating cell nuclear antigen (PCNA) immunohistochemistry, was confirmed in the gastric mucosa of ferrets experimentally infected with H. mustelae, which mimics H. pylori gastritis in humans (31). (14), and it has been suggested that a process favoring cell proliferation and survival over cell death may drive the carcinogenic process (2 (Table I). The incidences of disease (studies with H. hepaticus-related hepatitis) in Studies A-E are given in Table I.…”
Section: Introductionmentioning
confidence: 95%